To be in relation ancestors' or the polysemy of the Minangyan (Hanunoo) term apu - Luquin, Elizabeth (2006)
This article deals with the polysemy of the term 'āpu used by the Mangyan Patag of the Philippines, Minangyan language speakers. The anthropologists of the region usually translate the term 'apu as 'owner', 'master', and sometimes 'spirit possessor', 'leader'. They also define it as 'ascending kin (GEN-5, GEN-6, and GEN-7)' and stress the notions of property and ownership. And yet the problematic term 'āpu signifies more than a simple ownership relation. I will show in this article that these glosses are not entirely satisfactory. Rather than 'master' or 'owner', translations which seem to impoverish the polysemic senses, I will argue - giving some concrete examples - that the polysemy of the term 'āpu appears to imply more fundamental meanings. It turns out that we need to take into account that 'āpu means 'relation: ancestor', which organizes the relations between the living and the dead.
Includes bibliographical references (page 94).